PLEASE be with me: benefits of a peer-led supervision group for early career social work educators. Issue 2 (3rd April 2021) - Wenocur, Katharine; Page, Amy Preston; Wampole, Donna; Radis, Brie; Masin-Moyer, Melanie; Crocetto, Johanna
ABSTRACT: Junior social work faculty members face numerous challenges in adapting to their roles and preparing for continued work in academia. Many of these challenges center around the tasks of teaching and advising. Peer-led, mutual support groups offer an accessible and effective approach to facilitating growth. Such groups offer support that addresses several common challenges facing new faculty, primarily by helping to combat isolation, and facilitate group attachment. The article draws from literature on mutual aid groups; and provides several examples illustrative of group processes from a model version of the group.